In vivo and in silico studies of membrane-stabilizing and clot lysis activities of Trachyspermum ammi - Md. Showkoth Akbor; Mst. Farjanamul Haque; Ahmmed Zunaed Rahman; Manik Chandra Shill; Hossam Kamli; Catarina Martins Tahim; Ivo Cavalcante Pita Neto; Henrique D.M. Coutinho; Muhammad Torequl Islam (Food Chemistry Advances)
Trachyspermum ammi contains many important phytochemicals, including thymol, which is used to treat many diseases. This study aimed to check the membrane-stabilizing and clot-lysis capacity of the ethanol extract of T. ammi (ETA) and its main chemical component, thymol (THY). For this, we used hypotonic solution-induced erythrocyte lysing and egg-albumin protein denaturation for membrane-stabilizing capacity and human blood clot lysis for anti-atherombosis capacity. Further, we observed in silico study of THY and ntric oxide synthase (NOSs) isoform. The stabilizing effects of ETA and THY on the membrane changed depending on the concentration. At the highest concentration (160 μg/mL), they stopped the most bleeding, while the standard drug, acetylsalicylic acid, stopped less bleeding at the same concentration. In the erythrocyte lysing test, ETA showed 102.60 ± 0.01 and 75.83 ± 1.44% membrane protection. In the egg-albumin denaturation test, they showed 27.62 ± 0.02% and 56.71 ± 0.02% membrane protection, respectively. In our clot lysis experiment, ETA and THY also showed significant and concentration-dependent clot lysis capacity. The IC50 and EC50 values of THY were lower than ETA when it came to keeping the membrane stable and breaking up clots, respectively. In our in silico investigation, THY and NOSs showed significant binding interaction. Taken together, ETA and its major component, THY, exhibited potent membrane stabilizing activity and clot lysis activity in in vitro studies. Further studies are required to elucidate its other active principles and their biological effects, along with possible mechanisms.